Electrical circuits - Manning, Laurence A. (McGraw-Hill, 1966)
Chapter 1. Electrical - circuit quantities, Chapter 2. Circuits and circuit laws, Chapter 2. Exponential voltage and current functions, Chapter 4. Sinusoidal currents and complex numbers,...